2019
DOI: 10.3389/fnana.2019.00022
|View full text |Cite|
|
Sign up to set email alerts
|

Resting State Functional Connectivity of the Rat Claustrum

Abstract: The claustrum is structurally connected with many cortical areas.A major hurdle standing in the way of understanding claustrum function is the difficulty in assessing the global functional connectivity (FC) of this structure. The primary issues lie in the inability to isolate claustrum signal from the adjacent insular cortex (Ins), caudate/putamen (CPu), and endopiriform nucleus (Endo). To address this issue, we used (7T) fMRI in the rat and describe a novel analytic method to study claustrum without signal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…In contrast, shown in Figures 3E–G (see also bottom row of Supplementary Figure S2), a Cg cortex seed shows a strong connection specifically with the CLA in the awake state, but not insular cortex. This result is consistent with a recent rodent rs-fMRI study performed in a stronger magnetic field (7T), which reported that the CLA, but not insula, has functional connections with Cg cortex (Krimmel et al, 2019a).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, shown in Figures 3E–G (see also bottom row of Supplementary Figure S2), a Cg cortex seed shows a strong connection specifically with the CLA in the awake state, but not insular cortex. This result is consistent with a recent rodent rs-fMRI study performed in a stronger magnetic field (7T), which reported that the CLA, but not insula, has functional connections with Cg cortex (Krimmel et al, 2019a).…”
Section: Introductionsupporting
confidence: 92%
“…Because of the close proximity between the CLA and the surrounding insula, results produced by attempts at dissociating the functional connectivity between these two structures, even with higher magnet strengths in rodent studies (4.7–7T), must be interpreted cautiously (see new method by Krimmel et al, 2019a). We attempted to isolate the CLA from the insula in our study through seed-based analysis in an fMRI with a stronger field strength that allows for smaller voxel size.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in rodent and human imaging now also enable further isolation of claustral and insular activity. 130 , 131 Notably, the insula has been identified as a potential deep brain stimulation target for treatment of pain 132 , 133 ; it is possible that electrodes inserted for this purpose also have contacts within the claustrum or affect it via downstream activation. Despite the challenges of isolating claustrum activity during MRI, several studies of human brain activity during various modalities of experimentally induced pain report increased activity in the claustrum, among many other regions.…”
Section: Re-evaluating the Function Of The Claustrummentioning
confidence: 99%
“…It will be important for future studies to better delineate the precise roles of the claustrum and divisions of the insula, as well as their interactions, in pain. Recent advances in rodent imaging now also enable further isolation of claustral and insular activity (Krimmel, Qadir, et al, 2019;. Notably, the insula has been identified as a potential deep brain stimulation target for treatment of pain (Segerdahl et al, 2015;Galhardoni et al, 2019); it is possible that electrodes inserted for this purpose also have contacts within the claustrum or affect it via downstream activation.…”
Section: Painmentioning
confidence: 99%